1987
DOI: 10.1093/ajcn/45.5.946
|View full text |Cite
|
Sign up to set email alerts
|

The effect of starch-protein interaction in wheat on the glycemic response and rate of in vitro digestion

Abstract: To determine the effect on blood glucose of removal of protein from wheat products, healthy volunteers took test meals of white bread made from either regular or gluten-free flour. After bread made from gluten-free flour, the blood-glucose rise was significantly greater. This corresponded with a significantly more rapid rate of digestion in vitro and reduced starch malabsorption in vivo as judged by breath-H2 measurements. Addition of gluten to the gluten-free bread mix did not reverse these effects. Factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(125 citation statements)
references
References 26 publications
6
116
1
2
Order By: Relevance
“…In vitro method for measuring the rate of hydrolysis of starch has been suggested as an inexpensive and less time consuming method compared to measuring in vivo starch digestion (Jenkins et al 1987). O'Dea et al (1980) reported that in rice postprandial glucose and insulin responses correlate closely to the in vitro rates of hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro method for measuring the rate of hydrolysis of starch has been suggested as an inexpensive and less time consuming method compared to measuring in vivo starch digestion (Jenkins et al 1987). O'Dea et al (1980) reported that in rice postprandial glucose and insulin responses correlate closely to the in vitro rates of hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Factors affecting the rate of glucose absorption from starchy food and therefore the GI value include (1) the nature of the food and (2) the type and extent of food processing (Table 5). The former includes the ratio of amylose to amylopectin present in the raw food (Behall et al, 1988) and the type of monosaccharide components, the amount and type of dietary fiber (Jenkins et al, 1978), the presence of large amounts of fat or protein (Nuttall et al, 1984;Wolever et al, 1985;Collier et al, 1986;Bornet et al, 1987), antinutrients such as phytic acid, lectins and tannins (Yoon et al, 1983;Thompson et al, 1984;Rea et al, 1985) and nutrient -starch interactions in carbohydrate-containing foods, such as in wheat products (Jenkins et al, 1987a). Extrusion, flaking, grinding, canning, storing and cooking of the carbohydrate-containing foods can affect the particle size and the integrity of the starch granules (Jenkins et al, 1988a) and plant cell walls (Ellis et al, 1991), making the carbohydrate portion more accessible to digestive enzymes (Wolever, 1990;Collins et al, 1981).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…In the present study, we used gluten protein, comprising gliadins and glutenins, which are water absorbent, and exhibit network structures and starch-binding properties (Marshall and Chrastil, 1992). These properties can slow digestion and lower the increase in postprandial blood glucose (Jenkins et al, 1987). This explains why gluten protein can yield a more stable glycemic response and lower GI.…”
Section: Discussionmentioning
confidence: 99%
“…GIs are typically obtained by dividing the incremental postprandial blood glucose level by the corresponding level after ingesting an equivalent carbohydrate portion (25 or 50 g) of a reference food (Jenkins et al, 1983). Foods with a high GI are more rapidly digested and absorbed, causing greater fluctuations in blood glucose per unit of carbohydrate than foods with a lower GI (Jenkins et al, 1987). Studies showed that long-term consumption of high GI foods not only increased the risk of obesity, type 2 diabetes, and diabetic complications, but may also lead to heart disease and some types of cancer (McKeown, 1994;Salmerón et al, 1997;Ludwig et al, 1999;Liu et al, 2000;Augustin et al, 2002;Pi-Sunyer, 2002;World Health Organization, 2003;Schulze et al, 2004;Ebbeling et al, 2005;Wolever, 2006).…”
Section: Introductionmentioning
confidence: 99%